DAMPAK DEFISIENSI IODIUM MATERNAL PADA PERSISTENSI DISFUNGSI NEUROPSIKOLOGIS ANAK USIA 12 TAHUN (EFFECT OF MATERNAL IODINE DEFICIENCY ON THE PERSISTENCE OF NEUROLOGICAL DYSFUNCTIONS IN CHILDREN AGED 12 YEARS) - Budiman, Basuki; Djokomoeljanto, Djokomoeljanto; Suharyo, Suharyo; Ekowarni, Endang (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
ABSTRACT Study on the last effect of neuropsychologic dysfunction due to iodine deficiency during gestation is still scarce. This study is to confirm the persistence of neuropsychological dysfunctions at 12-year-old of children born from pregnant mothers with iodine deficiency in endemic iodine deficient area. The study is 13-year-cohort design. Iodine status (Total T4, TSH and UIE) of pregnant mothers at initial study, neonatal (TSH) and 12 year-old iodine status (fT4, TSH) are performed. Neurological dysfunction of infants is examined every 6 weeks until the child age is 24 months. Neuropsychological dysfunction of children 12 years of age such as minimal brain dysfunction and psychological battery of Wechsler Intelligence Scale for Children (WISC) are also administered. A screening to determine case and reference using is done using mini mental status examination (MMSE). Score MMSE of 28 or less are implemented as cases while others as reference. The relationship of neurological and cognitive dysfunction with both maternal iodine status and neurological dysfunction at 2 months of neonates age are elaborated. The persistency risk of neurological dysfunction at 12 years of age is 8% (95%ci: 1-15%). Maternal and neonatal iodine status (as indicated by TSH, T4) are the risk factors for the persistency at 12-years. However, delays of neurological development in two-month old infants are found as directly risk factors. Median Total IQ score for all participants are far lower than the lowest limit of normal range. A very significant difference (p=0.000) are found in Total IQ score between cases and references. Discrepancy analysis of IQV-IQP indicates brain lesions in subtle form, such as diadokhokinesis, praxis, memory, distractibility and lowered IQ score. Neuropsychological dysfunctions due maternal iodine deficiency are still persistence at 12 years. Maternal T4 during gestation is not only influences on the persistency but also impaires directly on the brain development of the progeny. Maternal TSH influences on neuropsychomotor development of infant only. Keywords: iodine deficiency, persistenci-neuropsychology, plasticity ABSTRAK Penelitian tentang disfungsi neuropsikologis berkelanjutan karena defisiensi iodium semasa ibu mengandung masih jarang. Mengonfirmasi persistensi disfungsi neuropsikologis pada anak 12 tahun akibat defisiensi iodium maternal di daerah endemik defisiensi iodium. Rancangan penelitian ini kohor 13 tahun sejak janin. Status iodium maternal awal penelitian diukur dari total T4, TSH dan EIU. Disfungsi neurologis bayi/anak diperiksa setiap enam minggu sampai bayi/anak berusia 24 bulan dengan INFANT IB, sedangkan disfungsi neuropsikologis anak 12 tahun diperiksa dengan uji neuropsikologis Mini Mental Status Examination (MMSE). Anak dengan skor MMSE < 28 disebut kasus dan sebaliknya. Hubungan disfungsi neurologis dan kognitif anak dengan status iodium awal kehamilan dan disfungsi neurologis bayi pada usia 2 bulan di analisis. Persistensi disfungsi neuropsikologis anak pada usia 12 ditemukan dengan risiko sebesar delapan persen (95%CI:1-15%). Status iodium ibu dan neonatus dengan indikator TSH dan T4 merupakan faktor risiko persistensi disfungsi neurologis pada umur 12 tahun. Keterlambatan perkembangan neurologis pada usia dua bulan ditemukan sebagai faktor risiko langsung terutama gangguan perkembangan tonus otot dan refleks postural. Median Intelligent Qoutient (IQ)-Total semua partisipan di bawah batas rentang normal. Median IQ Total kasus lebih rendah rujukan (p=0,000). Analisis diskrepansi IQV-IQP mengindikasikan adanya lesi otak dalam bentuk ‘halus’, seperti diadokokinesis, praksis, memori, mudah beralih perhatian (distractibility) danrendahnya tingkat kecerdasan. Persistensi disfungsi neuropsikologis masih ditemukan pada usia 12 tahun. Defisiensi iodium maternal selama kehamilan dengan indikator (T4) terbukti secara langsung berpengaruh terhadap persistensi disfungsi neurologis dan kognisi anak pada usia 12 tahun, sedangkan TSH maternal hanya berpengaruh terhadap perkembangan neuropsikologis bayi. [Penel Gizi Makan 2012, 35(1): 23-33] Kata kunci: defisiensi iodium maternal, persistensi-neuropsikologis, plastisitas